Influence of a Directional Dependenceon Mechanical Properties of Composites Reinforced with Chopped Carbon Fibre Produced by Additive Manufacturing - J. Majko; M. Handrik; M. Vaško; M. Sága; P. Kopas; F. Dorčiak; A. Sapietová (Archives of Metallurgy and Materials, 2023)
Progress in the industry is accompanied by the development of new materials and more efficient technological production processes. At present, additive production is becoming very attractive in all industries (research, development, production), which brings a number of advantages compared to subtractive methods (customization, production speed, control of material properties by users, etc.). The main advantage of 3D printing is the controlled deposition of material in defined places. Instead of demanding manual labour, fully automated production via computers leads to the manufacturing of complex components from materials whose production in conventional ways would be problematic or even impossible. Because these are new technologies, the main direction of research at present is to identify the basic physical properties of these materials under different types of loading. The main goal of this article is to observe the dependence of the behaviour of the extruded material (thermoplastic reinforced with chopped carbon fibre) on the printing parameters (thickness of the lamina, the orientation of the fibres of the printed material, etc.). Based on published scientific works, it appears that these settings have a significant impact on the achieved physical properties. This is the reason why the authors decided to analyze the influence of these parameters on the basis of processed data from experimental measurements of mechanical properties in the MATLAB program. As this is FFF printing, an essential condition is to identify and specify the directional dependence of the behavior of the printed material. This physical phenomenon is a necessary condition for gradual knowledge for the purposes of a subsequent mathematical description of the material properties. According to the authors, for the purposes of modeling these materials in FEM-based programs, it is essential to define the directional dependence in the plane of the lamina.